2021
DOI: 10.1016/j.carrev.2020.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Experience of ST Segment Elevation Myocardial Infarction Management During COVID-19 Pandemic From the Mainland of China

Abstract: Background The pandemic of COVID-19 has created a crisis in healthcare systems across the globe. This situation would affect the diagnosis and treatment of patients with STEMI. The outbreak was under improved control in the mainland of China. We here describe the impact of this pandemic on STEMI patient's management. Methods Information of STEMI patient management was collected from the CPC data reporting platform. We compared these with data of patients from the same p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Zhang et al 18 China Monocentric Good 395 n/a n/a n/a n/a n/a n/a n/a NIH: study quality as per the National Institutes of Health (NIH) Quality Assessment Tool. *Claeys et al: 16 baseline characteristics of 595 patients were assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al 18 China Monocentric Good 395 n/a n/a n/a n/a n/a n/a n/a NIH: study quality as per the National Institutes of Health (NIH) Quality Assessment Tool. *Claeys et al: 16 baseline characteristics of 595 patients were assessed.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Hebei Province was one of four provinces (Hebei, Hubei, Beijing, Tianjin) in China to Coronary artery disease maintain the national state of emergency the longest, thereby potentially contributing to a longer time to FMC. 18 Furthermore, studies from medical centres located in COVID-19 hot spots such as Milan, Italy, reported the most delayed FMC during the COVID-19 outbreak, suggesting a huge impact of local factors, such as fear, lockdown and possibly COVID-19-related structural deficits of the emergency care system. 8 15 Remarkably, the three studies included in our meta-analysis on time to FMC observing the largest prolonging effect of COVID-19 on FMC all derived from single centres, possibly accentuating local influences.…”
Section: Time To Fmcmentioning
confidence: 99%
“…130 Similarly, a study from China indicated a 51.4% decrease in hospital admissions of STEMI patients during the peak period of COVID-19 epidemic. 131 Importantly, lack of reperfusion therapy for STEMI patients was >10% higher in 2020 than the previous 2 years; 2-3 times more STEMI patients received fibrinolysis in 2020 than the 2 previous years, while the volume of primary PCI dropped by more than half. This led to highest mortality rate recorded in February 2020.…”
Section: Patient Delay In Seeking Care and Visiting The Emergency Department/re-emergence Of Post-mi Mechanical And Other Complications Imentioning
confidence: 99%
“…81 Thus, there is a reduced number of admissions for ACS but also a significant delay in ACS presentation consistently reported during the COVID-19 pandemic era. 7,130,131,136 There is fear supported by important preliminary evidence that this observed pattern may lead to increases in OOHCA, acute mechanical and long-term complications of MI and missed chance to implement secondary prevention therapies for patients with CAD. 127,128,135,136…”
Section: Patient Delay In Seeking Care and Visiting The Emergency Department/re-emergence Of Post-mi Mechanical And Other Complications Imentioning
confidence: 99%
“…Another study conducted in China showed that the number of primary percutaneous coronary intervention (PCI) dropped by more than a half in the first three months of 2020 compared to 2018 and 2019, while the number of patients treated with fibrinolysis increased by 2 to 3 times. Also in this study, a longer time to reperfusion was reported among patients treated in 2020 [ 28 ].…”
Section: The Epidemiology Paradox Of Acs In Covid-19mentioning
confidence: 62%